2019
DOI: 10.1002/adfm.201905996
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle Chains in Gelatin Ferrogels: Bioinspiration from Magnetotactic Bacteria

Abstract: Inspired by chains of ferrimagnetic nanocrystals (NCs) in magnetotactic bacteria (MTB), the synthesis and detailed characterization of ferrimagnetic magnetite NC chain-like assemblies is reported. An easy green synthesis route in a thermoreversible gelatin hydrogel matrix is used. The structure of these magnetite chains prepared with and without gelatin is characterized by means of transmission electron microscopy, including electron tomography (ET). These structures indeed bear resemblance to the magnetite as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…An important process is the formation of mesocrystals (an abbreviation of mesoscopically structured crystals), which consist of individual nanocrystals showing crystalline short-range order together with a mutual orientation leading to very interesting materials. These can show single crystalline and nanocrystal properties at the same time and can profit from the mutual order of the nanocrystals, which can, for example, lead to the coupling of magnetic dipoles just as it is observed in the magnetite nanoparticle chains in magnetotactic bacteria [13].…”
mentioning
confidence: 87%
“…An important process is the formation of mesocrystals (an abbreviation of mesoscopically structured crystals), which consist of individual nanocrystals showing crystalline short-range order together with a mutual orientation leading to very interesting materials. These can show single crystalline and nanocrystal properties at the same time and can profit from the mutual order of the nanocrystals, which can, for example, lead to the coupling of magnetic dipoles just as it is observed in the magnetite nanoparticle chains in magnetotactic bacteria [13].…”
mentioning
confidence: 87%
“…Another bioinspired study recently presented by Sturm et al showed similar ferrimagnetic magnetite nanochains that resembled the magnetosome chains found in magnetotactic bacteria [75]. Although the authors used a gelatin hydrogel to spatially separate the nanochains during their formation, it was not possible to exert control over the nanochains' lengths within the hydrogel matrix.…”
Section: Bioinspired Approaches For Magnetic Nanochain Synthesismentioning
confidence: 98%
“…However, one possible solution to this issue is based on the clustering of many superparamagnetic nanocrystals into larger nanoparticles that preserve the superparamagnetic properties, while possessing enhanced magnetic moment that is suitable for effective spatial guidance of the particles in suspension. Therefore, different approaches of superparamagnetic nanoparticle clustering have been proposed in the last two decades, including: one-pot nanoparticle cluster synthesis method, solvothermal methods, chemical cross-linking of nanoparticles in the cluster, preparation of composite nanoparticle clusters with polymers, and emulsion/evaporation-based clustering of hydrophobic nanoparticles, among other strategies ( Figure 6 ) [ 29 , 41 , 42 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Krasia-Christoforou et al has recently presented an elegant topical review on magnetic nanoparticle clustering that is available for further reading [ 88 ].…”
Section: Natural and Bioinspired Synthetic Approaches To Form Magnetic Nanochainsmentioning
confidence: 99%
“…With revolutionary developments of nanomaterials and bionics, smart actuators in response to natural muscles has attracted considerable attention in the last decade. Taking advantage of those functional materials with controllable shape or volume changes under external stimuli (such as light, heat, electricity, magnetism, humidity, and chemistry), smart actuators can convert such stimuli into mechanical energy in response to environmental stimuli ( Xu et al, 2015 ; Song et al, 2016 ; Shin et al, 2018 ; Li J. et al, 2019 ; Chortos et al, 2019 ; Sturm et al, 2019 ). Smart actuators have a wide range of application prospects in the fields of biomedicine, bionic robots, and smart medicine micro/nanomanipulators ( Zang et al, 2013 ; Yao et al, 2015 ; Santhiago et al, 2016 ; Hua et al, 2018 ; Power et al, 2018 ; Jia H. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%